The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fchem.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Reporter-Based Screens for the Ubiquitin/Proteasome System

Abstract: Instant and adequate handling of misfolded or otherwise aberrant proteins is of paramount importance for maintaining protein homeostasis in cells. The ubiquitin/proteasome system (UPS) is a central player in protein quality control as it operates in a seek-and-destroy mode, thereby facilitating elimination of faulty proteins. While proteasome inhibition is in clinical use for the treatment of hematopoietic malignancies, stimulation of the UPS has been proposed as a potential therapeutic strategy for various ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The effect of CBK77 was analyzed on additional reporters that represent different classes of proteasome substrates: ubiquitin-arginine-GFP (Ub-R-GFP), a soluble N-end rule substrate; YFP-CL1, an aggregation-prone substrate and lastly, a reporter based on the T cell receptor subunit CD3δ (CD3δ-YFP), which is degraded by ER-associated degradation (ERAD) [ 21 ]. Administration of CBK77, but not CBK07, resulted in accumulation of each of these substrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of CBK77 was analyzed on additional reporters that represent different classes of proteasome substrates: ubiquitin-arginine-GFP (Ub-R-GFP), a soluble N-end rule substrate; YFP-CL1, an aggregation-prone substrate and lastly, a reporter based on the T cell receptor subunit CD3δ (CD3δ-YFP), which is degraded by ER-associated degradation (ERAD) [ 21 ]. Administration of CBK77, but not CBK07, resulted in accumulation of each of these substrates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ubiquitin-arginine-GFP (Ub-R-GFP), a soluble reporter targeted for proteasomal degradation by the N-end rule pathway; YFP-CL1, which carries a C-terminal degradation signal that renders the reporter aggregation-prone and lastly, a reporter based on the T cell receptor subunit CD3δ (CD3δ-YFP), which is degraded by ERassociated degradation (ERAD) 16 . Administration of CBK77, but not CBK07, to three MelJuSo cell lines stably expressing these UPS reporters resulted in accumulation of each of these substrates, suggesting that CBK77 has a general inhibitory effect on the UPS (Fig.…”
Section: Cbk77 Causes Global Impairment Of the Upsmentioning
confidence: 99%
“…histolytica strain that express a GFP reporter substrate of UPS-mediated protein degradation. The ubiquitin-tagged GFP is cleaved in cells, and the free GFP undergoes ubiquitination by RING-E3 ubiquitin ligases for its subsequent degradation by the proteasome [ 50 ]. We found that mutant CSN5 overexpression disrupted protein degradation resulting in accumulation of GFP as measured by quantitative confocal imaging ( Fig 2F and 2G ) and fluorometric assay ( Fig 2H and S3H Fig ).…”
Section: Resultsmentioning
confidence: 99%